Reversed Phase High Pressure Liquid ChromatographicAnalysis of Ezetamibe in Pure and in Pharmaceutical Dosage Forms - Gowri Sankar, D.; Kumar, D.V.S.P. (Asian Journal of Chemistry, 2010)
A rapid, simple and precise reverse phase high performance liquid chromatography (RPHPLC) method was developed for the estimation of ezetamibe in pure form as well as in pharmaceutical dosage forms. The quantification was carried out using a BDSHypersil C-18 column 250 mm × 4.6 mm i.d. 5 μm particle size in isocratic mode, with mobile phase comprising phosphate buffer and acetonitrile in the ratio of 45 : 55 (v/v) at a flow rate of 1.0 mL /min. The eluent was monitored at 236 nm. The retention time was 4.118 min. The calibration curve was linear in the concentration range of 25–300 μg/mL and the percentage recovery ranged from 99.95–100.03.